PELAKSANAAN PENYULUHAN STUNTING ,SKRINING LAYAK HAMIL & PENGECEKAN KESEHATAN BALITA GUNA MENCEGAH TERJADINYA STUNTING, KECAMATAN KOTO KARI, KABUPATEN KUANTAN TENGAH, RIAU - Ramadatul Ilham; Ade Fitria; Louis Tabita Priscilia Giawa; Akti Velayuni; Ari Indah Elisabeth T; Fitri Desrianti Harahap; Indra Sukri; Ruben Jefri Siagian; Tri Fitri Ramadhani; Wita Lestari (Bajang Institute, 2023)
Stunting is a growth and development disorder experienced by children due to several factors characterized such as poor nutrition, recurrent infections, and inadequate psychosocial stimulation. There are several factors that cause stunting, namely chronic malnutrition and recurrent infections, exclusive breastfeeding, and low access to health including access to sanitation, clean water, and environmental health. The 2022 Indonesian Nutritional Status Survey (SSGI) results saw the prevalence of stunting in Indonesia drop from 28 % to 21.6%. The activity method is qualitative by applying several procedures: planning, preparation, and implementation. The results of this outreach can provide additional knowledge for mothers in Koto Kari village about the importance of preventing stunting